From shabby to chic: upscaling in the U.S. thrift industry - Raulli, Julie Ann, author; Raynalds, Laura T., advisor; Eitzen, D. Stanley, committee member; Taylor, Peter L., committee member; MacDonald, Bradley J., committee member (Colorado State University. Libraries, 2005)
This study investigates the upscaling process taking place in the U.S. thrift industry by examining three thrift firms located along Colorado's Front Range. It employs a multi-methodological approach to explore what this process entails, why it is occurring, and to evaluate its social and political implications. Participant observation in stores, in-depth interviews with industry personnel, and a survey of thrift store shoppers demonstrate that upscaling is occurring at this strata of consumption. The upscaling process entails: 1) changing the look of the stores so that they are cleaner, lighter, more organized, and made to appear more like their low-end retail competitors; 2) changing the merchandise, which now includes antiques as well as new goods purchased from trade markets and cast off by giant corporate retailers; 3) finding new locations for stores in suburban, high-traffic shopping centers rather than urban areas; and 4) a "McDonaldization" of thrift stores, which attempts to rationalize and make more efficient collecting, processing, distributing and pricing the used merchandise sold in these stores. This study finds that thrift firms are upscaling stores in order to attract middle-income consumers, a shift from the previously poor clientele. A review of popular magazines, books, and television programs illustrates how media destigmatizes the consumption of used goods making it fashionable to buy resale. This study shows, however, that changes in the thrift industry are occurring at a time when increasing income and wealth inequality in the United States makes purchasing used goods economically necessary for lower-income, middle-income, and even some upper-income shoppers. Together these trends render invisible social class inequities embodied and reproduced in the everyday practice of thrift shopping.
Keywords: sociology